Innovation of the Stunting Awareness Group in Efforts to Reduce Stunting Rates in Mallusetasi District, Barru Regency - Amalia, Dian Suci; Herman H; Suarlin; Haerul; Andi Anugrah Mahyuddin (Universitas Negeri Makassar, 2025)
The rapid development of technology has an impact on changes in human behavior in carrying out all activities. Activities that were originally carried out manually have transitioned into electronic, digital, and virtual forms. Along with the times, changes will always lead to something new, or commonly called innovation. The present study constitutes a qualitative study that aims to describe the innovation of the Stunting Awareness Group in efforts to reduce stunting rates in Mallusetasi District, Barru Regency. Data collection in this study was conducted through observation, interviews, and documentation. The informants involved were the Head of the Social Services Department, the Head of the Health Service, the Family Hope Program (PKH) Facilitator, the Stunting Awareness Group (Mpok Darti), and mothers who have toddlers. The results showed that the advantage of this innovation is the one-day, one-egg program; several agencies in Barru Regency that are competent according to their respective competencies collaborate to reduce the stunting rate in Barru Regency. Compatibility in the Stunting Awareness Group innovation to reduce stunting rates in Barru Regency is in accordance with the fulfillment of children's nutritional needs, namely eggs that contain protein. Complexity in the innovation of the Stunting Awareness Group to reduce stunting in Barru District is the lack of awareness and attention of parents about child nutrition, lack of environmental cleanliness and housing that can make the living environment less comfortable, poor availability of clean water and sanitation, and other things. The innovation of the Stunting Awareness Group to reduce stunting rates in Barru Regency is considered triable due to the collaboration with stakeholders involved in addressing stunting. The innovation of the Stunting Awareness Group in Barru District can be observed because there is monitoring from local governments such as the Head of Sub-District, Head of Village, Family Hope Program (PKH) assistants, and the Stunting Awareness Group (Mpok Darti). The intended evaluation, such as checking body weight, height, head circumference, and abdominal circumference in toddlers every month, and the results will be compared with before the implementation of this program innovation.